IMPULSY I INSTRUMENTY MONETARNE W KSZTAŁTOWANIU RELACJI MIĘDZY BANKIEM CENTRALNYM A SEKTOREM BANKOWYM - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 2008)
Monetary impulses consist in a change in the monetary category and are the effect of the central bank’s administrative decisions. They take the form of changes in the size of the monetary policy instruments applied. Those impulses are generated by the central bank using the monetary policy transmission mechanism and they predominantly induce certain behaviours of banking institutions. Consequently, the banking sector reacts to the monetary instruments being used by creating a more or less favourable financial environment for the real sphere, i.e. businesses and households. The type of monetary policy instruments, when they are applied as well as the power exercised through them by a central bank shape in different ways the relations of dependencies and independencies within the banking sector and its sensitivity to monetary impulses in different liquidity conditions.
MONETARY IMPULSES AND INSTRUMENTS IN THE SHAPING OF THE RELATIONS BETWEEN THE CENTRAL BANK AND THE BANKING SECTOR